Margaret's monsters - Heyes, Michael E. (Routledge, 2020)
The monastic Margaret : The life of St. Anthony and Gregory's Dialogues in the Life – In the belly of the beast : sexual surrender and resistance in the life – The Devil made me do it - audience partitioning and The life of St. Margaret – Circumcising Olibrius : threatening sexuality and religious alterity in The life of St. Margaret – Paging Dr. Margaret : prayers and pregnancy in The life of St. Margaret – Conclusion: The metamorphosis of monsters.
Includes bibliographical references and index
Keywords: Margaret; Christian women saints; Christian women martyrs; Monsters; Gender identity